Sophorolipids by the Starmerella bombicola as sanitizer in carcass washing by aspersion and immersion in slaughtering and poultry processing. (Research, Society and Development, 2021)
This work aimed to apply sophorolipids produced by the yeast Starmerella bombicola, as a sanitizer, in the washing water of poultry carcasses, simulating stages of slaughter and processing by spray and immersion of birds against the microorganisms Staphylococcus aureus, Escherichia coli, thermotolerant coliforms and mesophilic aerobes. For this evaluation, solutions of sophorolipids at 500, 2,250 and 4,000 µg.mL-1 applied to verify the antimicrobial effect. The evaluated results demonstrated that the most significant reduction in spray the most significant reduction was obtained when the solution containing 4,000 µg.mL-1 was sprayed, with a reduction of 1.32 for S. aureus, 1.47 for E. coli, 1.43 for thermotolerant coliforms and 1 .05 for mesophilic aerobes. In immersion water, the sanitizing action gradually increased exposure time. There was a total reduction of viable cells at 90 minutes with 2,250 μg.mL-1 of sophorolipids and 30 minutes of exposure to the concentration of 4,000 μg.mL-1. Sophorolipids showed an innovative potential against contaminating microorganisms in the poultry industry, and could be a new sanitizing agent bringing greater food security to products of the poultry industry.